A formal support group for esophageal atresia and/or tracheoesophageal fistula in South Africa may improve the outcome of these children and their families - de Vos, Corné; de Vos, Werner; Sidler, Daniel (Journal of Neonatal Surgery, 2021)
The psychosocial aspect of various congenital anomalies like esophageal atresia (EA) with/or without a tracheoesophageal fistula (TEF) being the cause of Post-traumatic stress disorder (PTSD), depression, and anxiety in parents of these children, is often overlooked by medical professionals. Support groups may be useful to address a part of this problem and form an important aspect of emotional support for any rare or congenital disease. A cross-sectional descriptive study was conducted to assess the need for a formal support group for parents of patients born with EA and to emphasize the role of emotional support for these parents and children. A questionnaire was sent to members of an informal WhatsApp group which included participants with diverse demographics across private and public platforms, across South Africa. The questions focused on 3 main areas: demographic data, diagnosis and the surgery, and information about the participant’s emotional support. All the data were inserted in an excel datasheet and descriptive statistical analysis was used. Questions were sent to 14 members of an informal WhatsApp group. Eight were included in the study. All 8 participants were mothers of children born with an EA with a TEF. The questions about the need for emotional support focus on the time after the baby was born. The majority (87.5%) of the mothers felt that they could bond with their babies during pregnancy, but in contrast, 75% felt that they missed an opportunity to bond with their babies after birth, mainly because they were not allowed to hold their babies for up to 11 days after birth. Only 1 of the mothers were in contact with other families with children born with EA, and 6 of the remaining 7 agreed that this would have helped them during this emotionally challenging time. All 8 thought that sharing their stories with others could have helped them emotionally and all agreed that an EA/TEF support group was a good idea. The family, as another patient, ought to be treated and included in the overall treatment plan if we aim to improve the quality of life for both the patients and their families. Disease-specific support groups can play a major role in the emotional well-being of both the children born with EA and their families.